2020
DOI: 10.1002/ijfe.2404
|View full text |Cite
|
Sign up to set email alerts
|

Causal relationship among international crude oil, gold, exchange rate, and stock market: Fresh evidence fromNARDLtesting approach

Abstract: There is a continuous debate on how commodity prices affect the stock prices of emerging countries. We contribute to this debate by study the causal relationship between international prices of crude oil, gold, exchange rate, and Indian stock market. India is one of the major oil and gold importing and major petroleum products exporting country. On the daily prices of all the above mentioned variables from "January 1994 to December 2019", the nonlinear autoregressive distributed lag model (NARDL) is employed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…Likewise, Monica and Santhiyavali (2017) reported the same result in India that there is a long-run relationship between exchange rate and gold prices. Likewise, Kumar et al (2020) investigated the dynamic association between the gold price and ERV They reported that gold prices affect ERV. Bashar and Kabir (2013) investigated the nexus between commodity prices and Australian dollar ERV and found that the increased commodity price volatility results in higher ERV.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Likewise, Monica and Santhiyavali (2017) reported the same result in India that there is a long-run relationship between exchange rate and gold prices. Likewise, Kumar et al (2020) investigated the dynamic association between the gold price and ERV They reported that gold prices affect ERV. Bashar and Kabir (2013) investigated the nexus between commodity prices and Australian dollar ERV and found that the increased commodity price volatility results in higher ERV.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, although research has been ample, few studies have focused on major importing countries such as India (Ram 2017;Kumar et al 2020). Moreover, relatively few studies have examined the impact of the RMB exchange rate on China's stock prices while adding the variable of global commodity prices, which has proven unignorable in more recent studies.…”
Section: The Effects Of Global Commodity Prices On Stock Pricesmentioning
confidence: 99%
“…They highlight that the dependence between oil and exchange rates is significantly negative during different periods of analysis. For a sample of emerging countries, Kumar et al (2020) study the causal relationship between international prices of crude oil, gold, exchange rate and Indian stock market using the nonlinear autoregressive distributed lag model. The findings of the study revealed that crude oil prices positively affect the Indian stock market and exchange rate negatively affects the stock market in the short run.…”
Section: Introductionmentioning
confidence: 99%